Searching for bioethical principles related to palliative care - Nunes, Lucília (2019)
In a society where cure and disease prevention are health services main objectives, it is crucial to consider the caring and follow-up of terminally ill patients, in favor of palliative care promotion and dissemination. Thus, in the approach to palliative care, there is a complexity of physical, psychological and existential factors, and to ethical principles must be considered when providing care. This theme brings several paths to explore, becoming very important to clarify palliative care, to reflect about specific principles (avoiding confusion with concepts such as euthanasia, assisted suicide, dysthanasia), trying to find the point of balance among many existing conceptions when we talk in end-of-life issues. It is also important to emphasize the importance of the family’s role and qualified health professionals, in a process of dignifying the patient, as autonomous, able to decide and for whom the finitude process that only makes sense with quality of life and relief from suffering, according to the beliefs and goals of life that holds.